Recent Advances on Natural Aryl-C-glycoside Scaffolds: Structure, Bioactivities, and Synthesis—A Comprehensive Review - Liu, Chen-Fu (Molecules (Basel, Switzerland), 2022)
Aryl-C-glycosides, of both synthetic and natural origin, are of great significance in medicinal chemistry owing to their unique structures and stability towards enzymatic and chemical hydrolysis as compared to O-glycosides. They are well-known antibiotics and potent enzyme inhibitors and possess a wide range of biological activities such as anticancer, antioxidant, antiviral, hypoglycemic effects, and so on. Currently, a number of aryl-C-glycoside drugs are on sale for the treatment of diabetes and related complications. This review summarizes the findings on aryl-C-glycoside scaffolds over the past 20 years, concerning new structures (over 200 molecules), their bioactivities—including anticancer, anti-inflammatory, antioxidant, antivirus, glycation inhibitory activities and other pharmacological effects—as well as their synthesis.